Pengaruh Kualitas Pelayanan Perpajakan, Kesadaran Wajib Pajak, dan Insentif Pajak terhadap Kepatuhan Wajib Pajak UMKM di Kota Binjai - Sulist Yowati Yuswadi Buulolo; Mittha Rizkina (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aimed to examine the influence of tax service quality, taxpayer awareness, and tax incentives on the tax compliance of MSME (Micro, Small, and Medium Enterprises) actors in Binjai City. The population in this study was not known with certainty; however, a total of 96 respondents were selected as samples using the Lemeshow formula. This research employed a quantitative primary data approach, which was collected through questionnaires and processed using SPSS Version 24. The analytical technique used was multiple linear regression analysis. The results of the study showed that tax service quality, taxpayer awareness, and tax incentives, both partially and simultaneously, had a positive and significant influence on taxpayer compliance in MSMEs in Binjai City. Tax service quality had a regression coefficient of 0.301, a t-value of 3.327, with a significance level of 0.001. Taxpayer awareness had a regression coefficient of 0.334, a t-value of 3.826, with a significance level of 0.000. Tax incentives had a regression coefficient of 0.238, a t-value of 3.042, with a significance level of 0.003. The results of the F-test showed an F-value of 108.094 with a significance level of 0.000. The critical values of t and F were 1.986 and 2.704 respectively, hence tcalculated > ttable and Fcalculated > Ftable with significance values < 0.05, thus the alternative hypotheses (Ha) were accepted and the null hypotheses (Ho) were rejected, indicating significant influence. These findings confirmed that hypotheses H1, H2, H3, and H4 were accepted and proven valid, as the results aligned with the proposed hypotheses. The most dominant variable influencing taxpayer compliance was taxpayer awareness, as it had the highest t-value. Approximately 77.2% of taxpayer compliance could be explained by tax service quality, taxpayer awareness, and tax incentives, while the remaining percentage was attributed to other external factors. Taxpayer compliance had a very strong relationship with tax service quality, taxpayer awareness, and tax incentives.